Pengaruh Penambahan Zat Aditif Virgin Coconut Oil (VCO) Terhadap Kualitas Plastik Biodegradable Berbasis Selulosa Bakteri –Gliserol dari Air Kelapa (Cocos nucifera) - Yudelta, Oltry; Putra, Ananda (Departemen Kimia FMIPA UNP, 2024)
Biodegradable plastic is environmentally friendly plastic because it is easily degraded by microorganisms. This research aims to see how much influence the addition of virgin coconut oil additives has on the quality of bacterial cellulose-Glycerol based biodegradable plastic from coconut water (Cocos nucifera) which includes physical properties test (moistur content and swelling test), mechanical properties test (tensile strength, elongation and elasticity) and biodegradation test. This research uses 3.5% Glycerol as a plasticizer with varying volumes of virgin coconut oil, namely 2 mL, 4 mL, 6 mL and 8 mL. The results of the physical properties test obtained are that the % moisture content and swelling test decreases as the volume of virgin coconut oil increases. The maximum results from mechanical properties testing obtained a tensile strength value of 118.97 MPa with variations in the addition of 6 mL virgin coconut oil, where the tensile strength value already complies with the SNI standard for synthetic plastics, namely in the range 24.7-302 MPa, , the elastic value obtained is 3571.15 MPa, and the elongation value is 5.28%. For the biodegradation test, the plastic that was added with virgin coconut oil experienced a decrease but on the 15th day this plastic has fully degraded.